Effects of variables on the production of red-fleshed pitaya powder using response surface methodology - Che Yunus, Mohd. Azizi (Penerbit UTM Press, 2011)
Central Composite Design technique from Response Surface Methodology (RSM) was used to investigate the effects of spray drying conditions on red-fleshed pitaya powder moisture content and bulk density. The spray drying independent variables and ranges are inlet air temperature (156-224oC), feed flow rate (16.6-33.4 ml/min) and maltodextrin concentration (31.6-48.4 %). Results showed that the data were adequately fitted to second order polynomial model. However, only linear terms proved to be significant for powder attributes. The best spray drying conditions within the experimental ranges for minimum powder moisture content of 3.88% would be inlet air temperature, feed flow rate and maltodextrin concentration of 224oC, 22.9 ml/min and 40% respectively. The maximum powder bulk density of 0.45 g/ml was obtained at inlet air temperature of 156oC, 16.6 ml/min feed flow rate and 48.4% maltodextrin concentration.